Ultra-processed food intake and diet carbon and water footprints: a national study in Brazil - Josefa Maria Fellegger Garzillo; Vanessa Fadanelli Schoenardie Poli; Fernanda Helena Marrocos Leite; Euridice Martinez Steele; Priscila Pereira Machado; Maria Laura da Costa Louzada; Renata Bertazzi Levy; Carlos Augusto Monteiro (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To study the association between ultra-processed food consumption and carbon and water footprints of the Brazilian diet. METHODS Cross-sectional analysis on data collected in 2008-2009 on a probabilistic sample of the Brazilian population aged ≥ 10 years (n = 32,886). Individual food intake was assessed using two 24-hour food records, on non-consecutive days. The environmental impact of individual diets was calculated by multiplying the amount of each food by coefficients that quantify the atmospheric emissions of greenhouse gases in grams of carbon dioxide equivalent (carbon footprint) and freshwater use in liters (water footprint), both per gram or milliliter of food. The two coefficients consider the food life cycle 'from farm to fork.' Crude and adjusted linear regression models and tests for linear trends assessed the association between the ultra-processed food contribution to total energy intake (quintiles) and the diet carbon and water footprints. Potential confounders included age, sex, education, income, and region. Total energy intake was assessed as a potential mediation variable. RESULTS In the crude models, the dietary contribution of ultra-processed foods was linearly associated with the carbon and water footprints of the Brazilian diet. After adjustment for potential confounders, the association remained significant only regarding the diet water footprint, which increased by 10.1% between the lowest and highest quintile of the contribution of ultra-processed foods. Additional adjustment for total energy intake eliminated this association indicating that the dietary contribution of ultra-processed foods increases the diet water footprint by increasing energy intake. CONCLUSIONS The negative impact of ultra-processed foods on the diet water footprint, shown for the first time in this study, adds to the negative impacts of these foods, already demonstrated regarding dietary nutrient profiles and the risk for several chronic non-communicable diseases. This reinforces the recommendation to avoid ultra-processed foods made in the official Brazilian Dietary Guidelines and increasingly in dietary guidelines of other countries.